Forging the Path to Tomorrow's Policing: Advancing a Progressive Higher Police Education System with Insights from Maluku Regional Police - Purwanti, Ani (Advances in Police Science Research Journal, 2024)
The educational method is widely acknowledged as crucial in attaining professionalization within law enforcement agencies and governmental bodies responsible for policing functions. This study aims to develop an advanced police education system by drawing insights from the experiences and observations of the Maluku Regional Police. The employed research methodology is the Qualitative Research Method, which encompasses data collection techniques such as interviews, focus group discussions, and content analysis. The study findings indicate that pertinent curricula, humanistic educational approaches, and transformative reforms within educational institutions characterize progressive education. The imperative for police education to adopt a progressive approach lies in its ability to cultivate critical thinking skills and foster open-mindedness among law enforcement employees. Individuals should be allowed to question and contest prevailing attitudes, behaviours, and policies that foster discrimination or marginalization. In order to facilitate the integration of modern police education, it is imperative to establish a strong collaborative relationship between law enforcement organizations and academic institutions. Academics must actively collaborate with law enforcement personnel through various means such as workshops, seminars, and other related activities.